2020
DOI: 10.31088/cem2020.9.1.64-70
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes of mitochondrial structure regulate steroidogenic activity of rat adrenal cortical cells

Abstract: Введение. Стероидогенная активность клеток надпочечников претерпевает существенные изменения в постнатальном периоде онтогенеза. Однако изменения структуры митохондрий кортикостероцитов при развитии коркового вещества надпочечников и вклад этих изменений в обеспечение секреторного процесса мало изучены. Цель настоящей работы -исследовать структурные изменения митохондрий кортикостероцитов в клубочковой, пучковой и сетчатой зонах коркового вещества надпочечника крысы в процессе постнатального развития и сопоста… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Enhanced aldosterone production after puberty by reduced ZG indicated increased functional load on the hormone-producing cells. Our previous study showed that ZG cells increased their functional capacity after puberty by reorganization of mitochondrial apparatus, which provides initial steps of steroidogenesis [ 36 , 37 ]. Accelerated secretory activity and reduced cell content are usually associated with more intensive cell renewal [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced aldosterone production after puberty by reduced ZG indicated increased functional load on the hormone-producing cells. Our previous study showed that ZG cells increased their functional capacity after puberty by reorganization of mitochondrial apparatus, which provides initial steps of steroidogenesis [ 36 , 37 ]. Accelerated secretory activity and reduced cell content are usually associated with more intensive cell renewal [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…After sexual maturation, rats show an increase in the production of aldosterone, in addition to a decrease in the size of the zona glomerulosa [ 78 ]. This happens due to partial reorganization of steroidogenesis, the mitochondrial apparatus; specifically, the replacement of large mitochondria with a larger number of smaller mitochondria [ 79 ]. Prenatal and postnatal exposure to low doses of DDT slowed the reorganization of mitochondria, and despite active growth of zona glomerulosa in the postpubertal period, the level of aldosterone in exposed rats remained low [ 67 ].…”
Section: Studies On the Effects Of Low Doses Of Ddt On The Adrenal Glandsmentioning
confidence: 99%